Application of geographic information system in ecotourism: a global bibliometric analysis - Amadua, Festus O.; Nhamob, Luxon; Benzougagh, Brahim; Turyasingura, Benson (Taylor & Francis Group, 2025)
The application of geographic information system (GIS) has significantly increased in ecotourism across diverse contexts. For example, GIS application is increasingly important in tourism through novel technologies like machine learning and remote sensing. Such applications can enhance sustainable tourism. However, analyses of the scope of GIS application in the overall ecotourism sector remain limited. Therefore, the objective of this study is to provide a comprehensive analysis of global research trends in GIS application to ecotourism through a bibliometric review of the literature. This study asks: to what extent is the application of GIS in ecotourism? An answer to this question can help researchers and policymakers to develop appropriate GIS programs and policies that can enhance sustainable ecotourism across context. To answer this question, we used VOSviewer to undertake a bibliometric literature review across scientific databases such as Scopus, Web of Science, and PubMed. We analyzed 789 publications from 1960 to 2022. Our search topics included authorship, co-authorship, countries, institutions & organizations. Results show an increased trend in global GIS applications in ecotourism, with useful implications for sustainability. It contributes to the Sustainable Development Goals (SDGs) in terms of Industry, Innovation, and Infrastructure (SDG 9), Sustainable Cities and Communities (SDG 11), Responsible Consumption (SDG 12), Climate Action (SDG 13) and Life on land (SDG 15).